Implementation Of Principal Transformational Leadership In Improving Teacher Performance In State Junior High Schools - Susilawati, Susilawati; Trisnamansyah, Sutaryat; Sauri, Sufyan; Saodih, Cahya (CV. Inara, 2022)
This research is motivated by the quality of education in Indonesia which is still static, especially in terms of the performance aspect of teachers as educators. The principal's leadership style is believed to be able to improve the performance of teachers who are considered less than optimal in improving the performance of junior high school teachers to be better and more focused according to transformational leadership indicators including programs, charisma, individual sensitivity, intellectual stimulation, and inspiration for principals in improving teacher performance at SMPN 167 and SMPN 234 Jakarta. In addition, the analysis is specifically aimed at finding out the obstacles and solutions for the principal's leadership in improving teacher performance. The research method used is descriptive qualitative research with a philosophical foundation of progressivism. The results of the study found that:(1) The principal program of SMPN 167 Jakarta in improving teacher performance refers to the main competencies, namely: pedagogic, personality, social, and professional. Meanwhile, the principal of SMPN 234 Jakarta added managerial competence to the program; (2) The transformational leadership charisma of principals at SMPN 167 and SMPN 234 Jakarta can be seen from the principal who is able to become a teacher figure, respects others, is an inspiration and is capable of making teachers prioritize common interests over personal interests; (3) The individual sensitivity of the principal can be seen in terms of being able to observe, appreciate and motivate teachers, such as some teachers being able to participate in the driving teacher program. (4) The principal's intellectual stimulus is found in the wide space in expressing opinions, updating the way of making rules and agreements, and modeling an innovative, hard working and professional attitude; (5) The principal's inspiration can be found when expressing the school's vision and mission; (6) In addition, the obstacles faced by school principals in improving teacher performance are weak human resources and inadequate infrastructure. SMPN 167 Jakarta also has obstacles regarding financing, there are still facilities that are not covered in the RKAS (7) The solution that can be given is that the principal can provide opportunities for teachers to attend certain workshops and training to support better teacher performance and better learning facilities. more comfortable for school residents, especially teachers. (5) The principal's inspiration can be found when expressing the school's vision and mission; (6) In addition, the obstacles faced by school principals in improving teacher performance are weak human resources and inadequate infrastructure. SMPN 167 Jakarta also has obstacles regarding financing, there are still facilities that are not covered in the RKAS (7) The solution that can be given is that the principal can provide opportunities for teachers to attend certain workshops and training to support better teacher performance and better learning facilities. more comfortable for school residents, especially teachers. (5) The principal's inspiration can be found when expressing the school's vision and mission; (6) In addition, the obstacles faced by school principals in improving teacher performance are weak human resources and inadequate infrastructure. SMPN 167 Jakarta also has obstacles regarding financing, there are still facilities that are not covered in the RKAS (7) The solution that can be given is that the principal can provide opportunities for teachers to attend certain workshops and training to support better teacher performance and better learning facilities. more comfortable for school residents, especially teachers.